Case report—CARMAT: the first experience with the Aeson bioprosthetic total artificial heart as a bridge to transplantation in a case of post-infarction ventricular septal rupture - Huenges, Katharina; Panholzer, Bernd; Cremer, Jochen; Haneya, Assad (Frontiers in Cardiovascular Medicine, 2023)
Background Post-infarction ventricular septal defects remain one of the most feared complications after myocardial infarction with high mortality rates. In special cases, surgical or interventional treatment strategies are technically not feasible and do not always lead to a good outcome. Case presentation A 58-year-old male patient in cardiogenic shock with a very large ventricular septal (VSD) defect (4.9 cm × 5 cm) due to myocardial infarction was presented in our department. Acute stabilization was achieved using peripheral venoarterial extracorporeal membrane oxygenation (VA-ECMO) support. Neither surgical nor interventional therapy was considered as a sufficient option due to the unsuitable anatomy of the VSD and the patient was listed for heart transplantation. After 2 weeks on ECMO, bleeding and infectious complications occurred. Due to organ shortage, urgent implantation of the bioprosthetic total artificial heart (TAH) Aeson device (CARMAT) remained the only useful strategy to achieve a mid- or long-term bridge to transplantation. After successful implantation and good recovery with the Aeson device, the patient was transplanted 4 weeks after implantation. Conclusion Post-infarction ventricular septal defects are highly challenging and are commonly associated with a poor prognosis. The implantation of the new Aeson TAH device is a promising therapeutic option, allowing a safe and long-term bridging to heart transplantation.